(untitled) (LEGAL DIALOGICA, 2026)
Abstract: This study aims to determine the extent of the effectiveness of legal regulations in handling acts of defamation through social media at the Makassar City Police Resort Office. This research is a normative-empirical legal study. It is a legal research method that combines a normative legal approach, namely the legal foundation in the form of laws and regulations in Indonesia, with empirical elements in the form of direct interviews conducted with law enforcement officers who are mandated by police regulations, particularly at the Makassar City Police Resort Office. The results of this study indicate that (1) the effectiveness of law enforcement in handling criminal acts of defamation through social media has not yet been considered fully effective. The increasing number of defamation cases through social media, which are regulated under the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 on Electronic Information and Transactions, aims to provide legal protection for individuals whose rights and dignity have been violated and to create a deterrent effect for perpetrators of defamation through social media. However, the expected law enforcement as a means to reduce criminal acts related to such cases has not yet shown a significant impact, as defamation cases are still frequently encountered. The recommendation of this study is that the public should be more aware of and comply with the existing legal regulations. Abstrak: Penelitian ini bertujuan untuk untuk mengetahui sejauh mana bentuk keefektivitasan aturan hukum terhadap tindakan pencemaran nama baik melalui media sosial pada Kantor Kepolisian Resort Besar Kota Makassar. Penelitian ini merupakan penelitian hukum normatif empiris. Yaitu metode penelitian hukum yang menggabungkan antara pendeketan hukum normatif yaitu landasan hukum berupa perundang-undangan di indonesia, kemudian digabungkan dengan unsur empiris berupa wawancara secara langsung oleh pihak aparat penegak hukum yang diberikan amanat oleh peraturan kepolisian, khususnya di kepolisian resort besar kota Makassar. Hasil penelitian ini menunjukkan bahwa (1) Efektivitas hukum dalam penanganan tindak pidana pencemaran nama baik melalui media sosial sejauh ini belum dapat dikatakan efektiv. Maraknya kasus pencemaran nama baik melalui media sosial yang diatur dalam Undang-Undang Republik Indonesia Nomor 19 Tahun 2016 tentang perubahan atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik adalah sebagai alat dalam memberikan perlindungan hukum terhadap seseorang yang dilanggar hak dan martabatnya serta guna memberikan efek jera terhadap pelaku pencemaran nama baik melalui media sosial.